Eldercare: A Mobile Application For Elderly Care - Yeow, Song Jie (2023)
According to a statement from the Department of Statistics Malaysia, the ageing population which is aged 65 years and above, is growing every year. In 2030, 15 per cent of barriers will be crossed whereas now it is only 7 percent. Among the elderly, about 85% of them owned a mobile phone and about 46% used a smartphone. Nowadays, mobile applications can bring convenience to society, especially for the elderly. The main problem is that the elderly has been forced to live alone while their children work in the city area. The safety and the emotions of the elderly need to be taken care of. They also will miss the right time to take medicine or the wrong portion. Due to the mentioned problem, the project is proposed with the main objective of providing an application focused on a mobile application for elderly care. The elderly and their family member can have the function of location tracking, a reminder of the medication, and emergency call in this application. The mobile application will acquire the internet to display and track the real-time location from and to the cloud database server. Rapid Application Development (RAD) has been chosen for the methodology of this project. Four phases are involved in the model to ensure that the application developed achieves the proposed objectives. To conclude, this project implements the Global Positioning System (GPS) and mobile technology, which can give basic elderly care for the elderly with several features in the application, such as real-time location tracking from anywhere and at any time, a reminder of medication and emergency call by using the mobile application that has been developed.